The Reevaluation of Intracranial Traumas Due to Life-Threating Criteria Which Doesn’t Have Clinical Findings: Case Report - Atan, Yusuf; Akbaba, Murat; Asıldağ, Mustafa Kenan; Tataroğlu, Zekeriya; Daş, Veysal (The Bulletin of Legal Medicine, 2018)
Gunshot wounds, towards to the head frequently ends with the fractures of the skull, brain hemorrhage and brain tissue damage. Each of these three injury types cause life-threatening due to the Turkish Penal Code, and they are usually seen together. As known, there are three basic foramens associated with cranium; superior and inferior orbital fissure and the optic channel which the optic nerve passes through. In presented case, a 39 years old female patient who was shot with a pump rifle (a kind of gunshot type) from her face and one pellet which does not produce any bone fracture or neurological symptom while passing the orbital pit, is presented. This case was found interesting because; even though these kinds of wounds are inside the criterias of life-threatening, in our case, the pellet which passes through the orbital pit did not produce any bone fracture, neurological symptom or brain tissue damage. In this study, it is aimed to discuss that should the life-threatening decision must be given just only according to the location of wound or should it be given according to the magnitude of damage?